Smart Village Desa Perlis: Improving Prima Village Services Based on Digital Applications - Qarni, Waizul; Jamila, Khaidar Rahmaini; Silalahi, Purnama Ramadani; Imsar, Imsar (LP2M INSURI Ponorogo, 2025)
This community service aims to realize a smart village in Perlis Village through a digital application. This study uses a participatory and collaborative approach. The activeness of participants and all stakeholders is needed from the planning stage to the evaluation. This community service is in Perlis Village, Berandan Barat District, Langkat Regency. The techniques for collecting and analyzing community service data are: 1) Smart Village Application and 2) Training using Smart Village Application software. The result of this service is an increase in the effectiveness of village services by 66% after using the smart village application. This shows the effectiveness of the training used significantly in providing knowledge to the community regarding administrative services for correspondence at the Perlis village office, which can be carried out online. Through the Perlis Village office, the village government is an agent of change for the self-reform process in empowering agents for the community to realize Smart Governance.